Zen Bloom / Farra Izziati Ayob ... [et al.]. - Ayob, Farra Izziati; Mohd Hambal, Hana Maisarah; Azman, Nur Athirah Ayuni; Razali, Nur Maisarah; Hariudin, Yasmin Natasya (2025)
In this increasingly urbanizing world, there is a growing demand for health and wellness products. Zen Bloom is a new invention of a portable plant pod that we designed specifically for today’s modern households, especially in the cities. This innovation meets the demand of people who want indoor plants that are easy to take care of that come with a number of healthy benefits. Aside from the product’s primary focus on improving the quality of indoor air, enhancing mental health as well as becoming beautiful aesthetics for home decorations, Zen Bloom seamlessly integrates technology with nature as an alternative to provide a practical solution to the people who are facing urban living challenges. Zen Bloom features some of the modern and advanced technologies, including oxygen-carbon dioxide sensor technology, which is responsible for monitoring the overall balance and quality of the air. Adaptive LED lighting is also one of the technology features that is necessary to maintain the plant health while also improving the ambient and mood of the room. A smart watering system is also being used to remotely manage the plant maintenance, which not only conserves water but also lessens the need for human supervision (Reghukumar & Vijayakumar, 2019). These technologies will ensure users have the chance to enjoy the air-purifying effects of rosemary and lavender among other plants, which give off relaxing scents and promote mental wellness. Our product is a very effective solution for people living in the cities who face problems such as air pollution, insomnia and anxiety as a co in a very stressful environment. As the rising number of individuals realising the importance of living a better lifestyle, Zen Bloom aims to position itself as an essential component in creating a calm, health-enhancing environment for this fast-paced urban lifestyles. By integrating ecological awareness into modern convenience, Zen Bloom makes indoor living healthier and provides a better appreciation for nature in today's fast-moving world.